Inside Cover: Enabling Lithium Metal Anode in Nonflammable Phosphate Electrolyte with Electrochemically Induced Chemical Reactions (Angew. Chem. Int. Ed. 35/2021). Issue 35 (21st June 2021) - Zhang, Haochuan; Luo, Jingru; Qi, Miao; Lin, Shiru; Dong, Qi; Li, Haoyi; Dulock, Nicholas; Povinelli, Christopher; Wong, Nicholas; Fan, Wei; Bao, Junwei Lucas; Wang, Dunwei
Abstract : An important challenge in the direct utilization of Li metal as an anode material for next‐generation batteries is the lack of stable solid electrolyte interphase layers. The problem is even more acute when non‐flammable electrolytes, such as organic phosphates, are used. In their Research Article on page 19183, Dunwei Wang and co‐workers report a new strategy that helps solve this issue. By introducing oxygen, the authors were able to induce unique chemical reactions that lead to safe operations of Li metal batteries that are flame‐resistant.